Using eDNA metabarcoding to understand the effect of fire on the diet of small mammals in a woodland ecosystem. Issue 11 (8th November 2022) - Wanniarachchi, Saumya; Swan, Matthew; Nevil, Paul; York, Alan
Abstract: Food acquisition is a fundamental process that drives animal distribution and abundance, influencing how species respond to changing environments. Disturbances such as fire create significant shifts in available dietary resources, yet, for many species, we lack basic information about what they eat, let alone how they respond to a changing resource base. In order to create effective management strategies, faunal conservation in flammable landscapes requires a greater understanding of what animals eat and how this change following a fire. What animals eat in postfire environments has received little attention due to the time‐consuming methodologies and low‐resolution identification of food taxa. Recently, molecular techniques have been developed to identify food DNA in scats, making it possible to identify animal diets with enhanced resolution. The primary aim of this study was to utilize eDNA metabarcoding to obtain an improved understanding of the diet of three native Australian small mammal species: yellow‐footed antechinus ( Antechinus flavipes ), heath mouse ( Pseudomys shortridgei ), and bush rat ( Rattus fuscipes ). Specifically, we sought to understand the difference in the overall diet of the three species and how diet changed over time after fire. Yellow‐footed antechinus diets mostly consisted of moths, and plants belonging to myrtles and legume families while bush rats consumed legumes, myrtles, rushes, and beetles. Heath mouse diet was dominated by rushes. All three species shifted their diets over time after fire, with most pronounced shifts in the bush rats and least for heath mice. Identifying critical food resources for native animals will allow conservation managers to consider the effect of fire management actions on these resources and help conserve the species that use them. Abstract : Information regarding diet changes over time after disturbance is lacking for many animals living in habitats prone to disturbances such as fires. DNA metabarcoding is a versatile molecular method that allows simultaneous characterization of many biotas using taxonomically informative barcode regions. In this paper, we utilized eDNA metabarcoding to obtain an improved understanding of the diets of three native Australian small mammal species: our results suggest that all three species shifted their diets over time after fire.